Pengembangan Platform E-Commerce Home Industry pada Oleh-oleh Khas Minang dengan Fokus pada OpenCart sebagai Solusi Pemasaran di Kabupaten Lima Puluh Kota - Wulan Dari, Putri; Annas, Firdaus (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Designing an E-Commerce Platform for Home Industry on Typical Minang Souvenirs with a Focus on Opencart as a Marketing Solution in Lima Puluh Kotse Regency aims to Design an E-commerce platform that can help Home Industry players in Lima Puluh city in marketing typical Minang souvenir products more effectively and efficiently. This article also aims to provide easier access for consumers to purchase typical Minang souvenir products through a platform built using opencart. Product marketing so far still uses a manual system and its reach is still not wide to be known to the wider community, only known by the surrounding community. Whereas in today's digital era Home Industry marketing can be recognised by the wider community using online sales media social media through sales sites on the internet. The research method applied is the Research and Develop (R&D) model, using needs analysis, system design, and prototype testing. The results of this study indicate that the development of an e-commerce platform using OpenCart for the Kahs Minang sanjai food home industry in Lima Puluh Kota Regency has succeeded in increasing marketing and sales effectiveness. The designed system facilitates transactions, allows users to access product information quickly, and provides transactions, allows to access product information quickly, and provides accurate sales reports. With this platform, businesses can reach a wider market and increase customer satisfaction through the convenience of online shopping. Overall, the implementation of e-commerce contributes to business growth and sustainability of local industries.